X-ray diffraction and Mössbauer spectrometry studies of molecular iron compounds - Costa, B. F. O. (2007)
We have synthesized two new iron complexes that have been structural and magnetically characterized: diphenylguanidinium hexafluoroferrate and hexakisvaline-oxo-triiron(III) chloride. The former crystallizes as monomers with the fluoride ions six-coordinating the Fe(II) ion. Valine iron chloride is comprised of trinuclear complexes, with a well ordered oxo-centered carboxylate core and some disordered organic ligands. The magnetization curves show a paramagnetic behavior. The Mössbauer measurements as a function of temperature show a paramagnetic behavior at 300 K with two Fe sites (one quadrupolar doublet and a broad single line). At 4.2 K, besides the quadrupolar doublet there is a magnetic component which can be attributed to a slow relaxation phenomenon associated to these samples.